Mapping the landscape of vernacular architecture research in Indonesia: A bibliometric analysis - Ratodi, Muhamad; Syariah, Arfiani; Hapsari, Oktavi Elok; Widiastuti, Mega Ayundya; Ernawati, Rita (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2024)
The evolution of Indonesian vernacular architecture research is examined using bibliometric analysis. We investigate publishing trends, authorship patterns, thematic focuses, and geographical distribution of research from 2000 to 2024 using Scopus data from 89 publications. Since 2015, research on sustainability, cultural identity, and preservation has increased significantly. Analysis shows a fragmented research community with room for more collaboration, especially between domestic and international organizations. Java and Bali are the most researched, indicating a geographical imbalance. Disaster resilience, digital documentation, bioclimatic performance, sustainable tourism, and vernacular urban adaptation are trends. The study finds research gaps, notably in eastern Indonesia, and advises additional research. Researchers, policymakers, and practitioners studying and preserving Indonesia's rich architectural legacy can benefit from this comprehensive review. This project maps the present research landscape to assist future research and preserve Indonesian vernacular architecture.